2021
DOI: 10.1016/j.jmapro.2020.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Consideration of SLM additive manufacturing supports on the stability of flexible structures in finish milling

Abstract: The supports in additive manufacturing can be used in an innovative way by being considered as supports for machining operation. This innovative use of manufacturing supports can facilitate the finishing of functional thin structures. But the flexible global workpiece-supports system can potentially cause vibrations during the machining operation. This can cause irregular surfaces with bad quality.This study highlights the importance of additively manufactured support structures on the stability of Ti-6Al-4V p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 29 publications
(39 reference statements)
0
9
0
Order By: Relevance
“…Lattice structures are three-dimensional structures consisting of one or more repetitive unit cells (Cheng et al, 2018;Zhang et al, 2018;Feldshtein et al, 2019;Blakey-Milner et al, 2021;Kas and Yilmaz, 2021;Zheng et al, 2021). These structures can be named as cellular solids, cellular metals, cellular foams (Pan et al, 2020), lattice sequences (Didier et al, 2021), porous structures (Łyczkowska et al, 2014) or scaffold structures (Wauthle et al, 2015). Lattice structures have higher energy absorption, sound insulation and heat capability than solid structures.…”
Section: Lattice Structuresmentioning
confidence: 99%
“…Lattice structures are three-dimensional structures consisting of one or more repetitive unit cells (Cheng et al, 2018;Zhang et al, 2018;Feldshtein et al, 2019;Blakey-Milner et al, 2021;Kas and Yilmaz, 2021;Zheng et al, 2021). These structures can be named as cellular solids, cellular metals, cellular foams (Pan et al, 2020), lattice sequences (Didier et al, 2021), porous structures (Łyczkowska et al, 2014) or scaffold structures (Wauthle et al, 2015). Lattice structures have higher energy absorption, sound insulation and heat capability than solid structures.…”
Section: Lattice Structuresmentioning
confidence: 99%
“…The supports must have a mechanical strength suitable for this machining operation so as not to deteriorate the surface quality of the manufactured part. Therefore, a previous study [21] has shown that surface qualities and dimensional deviations depend on the support structures. The choice of supports must be considered as a key step in the associated digital chain of the additive manufacturing flux.…”
Section: Introductionmentioning
confidence: 97%
“…This support method, which allows for the most stable and wa free manufacturing possible, is often used in Powder Bed Fusion (PBF) of metals (e Selective Laser Melting-SLM, Direct Laser Metal Sintering-DLMS, Electron Beam M ing-EBM, etc.) [15][16][17][18][19] and Vat Photopolymerisation (VPP, e.g., Stereolithography-S Digital Light Processing-DLP, etc.). Similar is the case of the filling of bodies with lar volumes, or the connection of two separate walls.…”
Section: Introductionmentioning
confidence: 99%